Optimization of Photovoltaic Performance Through the Implementation of a Photodiode-Controlled Dual-Axis Solar Tracking Mechanism - Dewi, Riyani Prima; Saepul Rahmat; Betti Widianingsih; Gilang Saputra; Afrizal Abdi Musyafiq; Novita Asma Ilahi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
Indonesia has abundant renewable energy resources that support efforts toward energy independence and long-term energy security. However, photovoltaic (PV) modules are commonly installed in a fixed orientation, which limits solar energy absorption as irradiance varies with the sun’s position. To address this issue, this study employs a photodiode-based dual-axis solar tracking system capable of continuously aligning the panel with the sun’s trajectory. The photodiodes detect the direction of incoming sunlight, enabling real-time orientation adjustments to improve energy harvesting. Experimental results show that the dual-axis tracker produces an average output of 20.51 V and 0.98 A, compared to the static PV module with 19.97 V and 1.07 A.